Use of Imatinib Mesylate in the Management of Chronic Myeloid Le ukaemia - Kamal, SM; Ahad, MA; Mahmood, I (TAJ: Journal of Teachers Association, 2009)
lmatinib mesylate (Enliven) is a synthetic tyrosine kinase inhibitor. If inhibits the break point cluster region (BCR)-Abelson (ASL) fusion protein that results from the chromosome abnormality known as the Philadelphia chromosome which leads to increased cell proliferation in chronic myeloid leukaemia (CML). lmatinib is approved for the treatment of Philadelphia chromosome positive (Ph+ ) chronic myeloid leukaemia (CML). Response is good with high 5 years survival rate. It is well tolerated. lmatinib is also recommended for the treatment of Gastro intestinal stromal tumour (GIST), Philadelphia positive acute lymphoblastic leukaemia (ALL) and nephrogenic systemic fibrosis (NSF). Use of imatinib in CML is discussed in this review article. TAJ 2009; 22(1): 315-318